Hsp90 and its co‐chaperone Sti1 control TDP‐43 misfolding and toxicity. Issue 5 (28th April 2021) - Lin, Lilian Tsai‐Wei; Razzaq, Abdul; Di Gregorio, Sonja E.; Hong, Soojie; Charles, Brendan; Lopes, Marilene H.; Beraldo, Flavio; Prado, Vania F.; Prado, Marco A. M.; Duennwald, Martin L.
Abstract: Protein misfolding is a central feature of most neurodegenerative diseases. Molecular chaperones can modulate the toxicity associated with protein misfolding, but it remains elusive which molecular chaperones and co‐chaperones interact with specific misfolded proteins. TDP‐43 misfolding and inclusion formation are a hallmark of amyotrophic lateral sclerosis (ALS) and other neurodegenerative diseases. Using yeast and mammalian neuronal cells we find that Hsp90 and its co‐chaperone Sti1 have the capacity to alter TDP‐43 misfolding, inclusion formation, aggregation, and cellular toxicity. Our data also demonstrate that impaired Hsp90 function sensitizes cells to TDP‐43 toxicity and that Sti1 specifically interacts with and strongly modulates TDP‐43 toxicity in a dose‐dependent manner. Our study thus uncovers a previously unrecognized tie between Hsp90, Sti1, TDP‐43 misfolding, and cellular toxicity.